Ghana privatises cocoa exports - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Government of Ghana has announced the privatisation of the Cocoa Product Buying Company, the central purchasing and export agency for about 70% of national production. With a production of 409,000 tonnes of cocoa beans in 1998-1999, Ghana is...